Aerodynamics of unconventional airfoils - actuation force of variable cambered airfoil - Chan, Adil Arif. (2010)
In the design of a morphing wing mechanism, actuation costs need to be taken into consideration. The energy required for the morphing can be reduced or increased depending on the nature of the morphing and also the speed at which the morphing occurs.